The utility of tumor markers and neutrophil lymphocyte ratio in patients with an intraoperative diagnosis of mucinous borderline ovarian tumor. (January 2016) - Seckin, Kerem Doga; Karslı, Mehmet Fatih; Yucel, Burak; Bestel, Melih; Yıldırım, Dogukan; Canaz, Emel; Akbayır, Ozgur
Abstract: Objective: To evaluate the utility of tumor markers and complete blood count to increase the diagnostic accuracy to detect malignant cases that are intraoperatively reported as mucinous borderline ovarian tumors (BOT). Study design: Patients who underwent laparotomy at our gynecologic oncology clinic between 2007 and 2015 for evaluation of an adnexal mass with an intraoperative frozen section report of mucinous BOT were retrospectively analyzed. Patients were grouped according to the final pathological diagnoses (malignant, borderline and benign), and were compared in terms of tumor marker levels and complete blood count parameters. Significant parameters were evaluated together with frozen section results, and were assessed for diagnostic accuracy. Results: A total of 63 patients were included in the study. Of these, 41 patients had borderline, 11 patients had benign, and 11 patients had malignant mucinous ovarian tumors. Patient age, menopausal status, hemoglobin, platelet and lymphocyte counts were similar among the groups ( p > 0.05). On the other hand, white blood cell, neutrophil counts and neutrophil/lymphocyte ratio (NLR) were significantly higher in malignant cases ( p < 0.05). Similarly, CA125 and CA19-9 were significantly higher in malignant group ( p < 0.05). When evaluated with the frozen section results, CA19-9 and NLR had the highest sensitivity to detect mucinous cancers (81 and 78 percent, respectively). Conclusions: In patients who have an intraoperative frozen section diagnosis of borderline mucinous ovarian tumors, CA19-9, NLR and CA125 were significant predictors of malignancy. In light of larger future studies, we believe that integrating these parameters into routine clinical practice may decrease the rate of under diagnosis.